Understanding the influence of stratification for mine water management: a comparative study - Elke Mugova; Christian Wolkersdorfer (Scientific Reports)
Abstract Managing mine water in the best possible way is of great importance and depends on various factors like environmental protection, regulatory compliance and human health. To understand the complex chemical and hydrodynamic processes within the mine pool, it is critical to establish effective practices and management strategies. This study focuses on the characterisation of hydrodynamic processes affecting flooded underground mines, emphasising the importance of density stratification. The investigation of 29 ore and coal mine shafts and their corresponding physico-chemical depth profile measurements was aimed to compare the profiles with each other, while also taking into account the shaft geometry and the layout of the mine. Finding cross-links between the profiles, which allow universal statements on stratification in flooded underground mines, was the main objective. Results of this study indicate that stratification occurs in almost all flooded underground mines, and the uppermost stratified water body is usually located in the area of the first or second connected level. Furthermore, stratification is often responsible for considerably better quality of the uppermost water body. Hence, stratification is fundamental to mine water management and has a direct influence on the quality of the discharged water. This knowledge is invaluable in developing strategies to optimise mine closure, mine water management, treatment planning and future mine layouts.